Kebimbangan ujian dan motivasi dalam kalangan pelajar kursus Bahasa Arab dalam konteks kemahiran lisan - Ghazali Yusri,; Nik Mohd Rahimi,; Parilah M. Shah, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The Arabic Language course in MARA University of Technology (UiTM) is an elective offered undergraduate students. The purpose of this study was to investigate the level of test anxiety, and intrinsic and extrinsic motivation of oral Arabic among students who enrolled in the Arabic courses in UiTM Shah Alam, Malaysia. The objectives were to investigate (1) the level of test anxiety, and intrinsic and extrinsic motivation among students and (2) the level of correlation between test anxiety, and intrinsic and extrinsic motivation for the oral Arabic test. This study was carried out quantitatively using an adapted questionnaire from The Motivated Strategiesfor Learning Questionnaire (MSLQ). A number of 279 students were chosen based on stratified random sampling. The study found that (1) the level of test anxiety among students was moderate while the level of both intrinsic and extrinsic motivation were high. (2) Extrinsic motivation was found to be positively and significantly correlated to instrinsic motivation and the correlation value was moderate. On the other hand, there were no significant correlations found between these motivations and test anxiety. Suggestions of ways to overcome test anxiety among students were given in order to sustain the level of intrinsic and extrinsic motivation in Arabic teaching and learning